FORMULASI DAN EVALUASI SABUN PADAT MINYAK ADAS BINTANG (Illicium verum) DENGAN VARIASI KONSENTRASI MINYAK KELAPA, MINYAK SAWIT DAN MINYAK ZAITUN - Azzahra, Fauzia; Ramadhani, Intan Puspita; Fitriani, Rima; Mayuri, Nindya Sekar (Jurnal Inkofar, 2025)
Soap bar is a cleansing preparation created by the saponification reaction. The qualities of soap bars vary depending on the oil composition. Furthermore, additional materials, such as essential oils, could be added to boost the product's value and benefits. The aim of this study is to generate good-quality soap bars using Illicium verum as active ingredients and varying oil concentrations applying the cold process method. The developed soap bar was then examined for its organoleptic properties, pH, moisture content, foam stability, and free fatty acid. On the 7th day, F1, F2, and F3 had pH values of 10.36 ± 0.012, 10.30 ± 0.038, and 10.15 ± 0.095, moisture content (%) of 5.21 ± 0.16, 4.76 ± 0.40, and 7.80 ± 0.58, foam stability (%) of 89.4 ± 0.06, 72.9 ± 0.07, and 74.8 ± 0.10, and free fatty acid (%) of 0.342 ± 0.024, 0.301 ± 0.024, and 0.328 ± 0, respectively. On the 14th day, F1, F2, and F3 had pH values of 10.09 ± 0.121, 10.29 ± 0.015, and 10.18 ± 0.067, moisture content of 4.55 ± 0.46, 3.49 ± 0.29, and 6.67 ± 0.29, foam stability of 91.3 ± 0.02, 91.7 ± 0.05, and 86.2 ± 0.04, and free fatty acid of 0.478 ± 0.063, 0.586 ± 0.046, and 0.560 ± 0.024, respectively. Both the results from the 7th and 14th days comply with the specifications. The variation in oil concentration influences soap bar qualities such as organoleptic, moisture content, and pH.Keywords : Soapbar, Illicium verum, Coconut oil, Palm oil, Olive oil